Propionic Acid Metabolism During Anaerobic Biowaste Slurry Digestion - Sembiring, Tarzan; Ekoputranto, Agung; Sriwuryandary, Lies; Nilawati, Dewi; Gallert, C; Winter, J (Teknologi Indonesia, 2012)
Solid waste was found to be a problem in the city sanitary and river management in Indonesia. Bio-waste from traditional market, which is as the major part of the solid waste of the city, is one of the big problem in the sanitary management. To over come of the problem of the bio-waste, the experiment on the anaerobic biodegradation of organic waste slurry in stirred tank bioreactor was executed. The substrate was feeding into reactor and inoculated with an anaerobic enriched mixed culture originally from cow intestinal micro flora. The total solid of substrate was around 10 percent. During the batch experiment showed that the pH value relatively stable around pH 7 but the pH is decreased in the end of the experiment. The degradation of organic slurry is shown by the decreasing of COD content from around 90 g/l to 20 g/l and the formation of volatile fatty acids. Methane content of the biogas produce is more than 60 %. The volatile fatty acids detected are acetic acid, propionic acid, butyric acid and valeric acid. The fluctuation of volatile fatty acids formation and its depletions were relatively good as well as the depletion of Chemical Oxygen Demands, in which the pH value is around 7.5 Propionic acid and butyric acid degrading bacteria were also found in the consortium of mixed culture as indicated by the elimination of those volatile fatty acids during the experiment and in the enrichment cultures. Observation of the cultures of propionic acid degrading enrichment under the microscope shown that the morphology of the bacteria were rod with dimension of 0.81 ?m x 2-3 ?m ( d x l ) and the better gown in pH 6.57.